High-intensity ultrasound processing of baobab fruit pulp: Effect on quality, bioactive compounds, and inhibitory potential on the activity of α-amylase and α-glucosidase - Ismail, Balarabe B.; Liu, Donghong; Pu, Yunfeng (Elsevier, 2021)
Effect of high-intensity ultrasound (HIU) compared with thermal treatments on baobab fruit pulp (BFP) quality and bioactive properties were investigated. HIU treatments, particularly at intensities of 687.5 W/cm2 for 5 min, and 344 W/cm2 for 15 min significantly (p < 0.05) increased the cloudiness index, ascorbic acid (AA) retention, total phenolic and flavonoid contents, and antioxidant capacity besides a more potent α-amylase and α-glucosidase inhibition relative to thermally treated samples. Moreover, the physicochemical parameters, colour index, and browning index were maintained with HIU besides lower 5-hydroxymethylfurfural values than thermal processing. HPLC analysis revealed that the content of most phenolic compounds was the highest in HIU treatments besides a 235–256% increase in procyanidin C1 compared with control samples. The AA retention following HIU treatments was 87.62–102.86% compared to 30.47–61.90% in thermally treated samples. Our analyses portrayed ultrasound as a feasible alternative to conventional thermal processing of BFP.
Food Chemistry, 361, 130144.
Keywords: Qiao He; Mingming Guo; Baobab fruit pulp; High-intensity ultrasound; Bioactive compounds; Ascorbic acid; Proanthocyanidins; Antioxidant capacity; CDA; Bayero University, Kano; Nigeria